Strategic management of nano-fertilizers for sustainable rice yield, grain quality, and soil health - Sahoo, Bignyan Ranjan; Dash, Ashish Kumar; Mohapatra, Kiran Kumar; Mohanty, Shraddha; Sahu, Suman G.; Sahoo, Bidwan Ranjan; Prusty, Meenakhi; Priyadarshini, Elora (Frontiers in Environmental Science, 2024)
Conventional fertilizers, though widely available are relatively low in nutrient use efficiency and cause serious environmental concerns like eutrophication, greenhouse gas (GHG) emissions, nitrate poisoning, and soil pollution. With this in mind, a randomized block design (RBD) experiment was conducted in a experimental field taking ten treatments and three replications to investigate the effects of integrated approaches of nano-formulated DAP fertilizer application on rice growth, yield, and nutrient use efficiency over conventional approaches. The result revealed that plant height, panicle length, number of tillers hill -1 , total number of grain panicle -1 , and root length were maximum in T10 treatment (50% of soil test recommended dose (STD) for N and P + seedling root dipping (SRD) with nano-DAP @ 5 ml L -1 + twice-foliar spray (FS) with nano-DAP @ 4 ml L -1 at 25 and 45 DAT(Date after Transplanting ). The highest mean grain yield (4.12 and 4.05 Mg ha -1 ), and nutrient uptake were recorded in the T2 treatment (100 % STD) but this was at par with T10 treatment. The highest benefit-cost ratio (2.26) was recorded in T10, which was 3.5% higher than T2. N and P agronomic use efficiency (AUE) ranged from 7.5-31.5% and 15-63%, and recovery efficiency (RE) ranged from 30-94.2% and 11.2-90.4%. The highest nutrient use efficiency was recorded with T10, followed by T9, and lowest in T4. Post-harvest soil pH as well as available N and P were significantly highest in T10. Soil MBC, MBN, MBP, urease, phosphatase activity were found significantly higher in T2 follwed by T10. The Integrated application of 50% STD for N and P + SRD with nano-DAP @ 5 ml L -1 + twice FS with nano-DAP @ 4 ml L -1 at 25 and 45 DAT application can be a suitable substitute for conventional DAP and Urea for rice in climatesmart agriculture, as it possibly reduces environmental pollution while undisturbing crop yield over the 100% STD.